A Combined Crystallographic and Theoretical Study Explains the Capability of Carboxylic Acids to Adopt Multiple Binding Modes in the Active Site of Carbonic Anhydrases. Issue 1 (30th November 2015) - Langella, Emma; D'Ambrosio, Katia; D'Ascenzio, Melissa; Carradori, Simone; Monti, Simona M.; Supuran, Claudiu T.; De Simone, Giuseppina
Abstract: Carboxylates are the least investigated class of inhibitors of carbonic anhydrases (CAs). Here we explain the versatility of binding of these molecules to CAs by examining a new adduct of hCA II with N‐carboxymethyl‐saccharin. Abstract : Mapping enzymes : Carboxylates are the least investigated class of inhibitors of carbonic anhydrases (CAs). Here we explain the versatility of binding of these molecules to CAs by examining a new adduct of CA II with N ‐carboxymethyl‐saccharin (see figure).